2016
DOI: 10.15390/eb.2016.4639
|View full text |Cite
|
Sign up to set email alerts
|

A Model of Decision-Making Based on Critical Thinking

Abstract: ÖzAnahtar Kelimeler

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 71 publications
0
8
0
Order By: Relevance
“…Therefore, in simple words, inquisitiveness refers to learners' curiosity or eagerness to acquire own understanding in learning process. Uluçınar and Aypay (2016) supported that inquisitiveness can be used as a powerful tool to guide individuals' actions and motivates their behaviors towards solving uncertainties and reveal the unknown. One of the distinctive and defining features in inquisitive learning is questioning.…”
Section: Inquisitive Learningmentioning
confidence: 96%
See 2 more Smart Citations
“…Therefore, in simple words, inquisitiveness refers to learners' curiosity or eagerness to acquire own understanding in learning process. Uluçınar and Aypay (2016) supported that inquisitiveness can be used as a powerful tool to guide individuals' actions and motivates their behaviors towards solving uncertainties and reveal the unknown. One of the distinctive and defining features in inquisitive learning is questioning.…”
Section: Inquisitive Learningmentioning
confidence: 96%
“…Once the instructors provide the answers, they will continue learning at own pace, even outside the classroom. According to Uluçınar and Aypay (2016), there are various theories proposed in the literature to explain what inquisitiveness is and how it arises. The first theory given by Berylne (1966, as cited in Uluçınar & Aypay, 2016 referred inquisitiveness as a humane urge, like hunger or thirst, that triggers learning information.…”
Section: Inquisitive Learningmentioning
confidence: 99%
See 1 more Smart Citation
“…The decision-making process is adapted to fit the purpose of the decisions being made, whether they are socioscientific issues, designs choices, or personal needs; how we make the decision is vitally important. Enhancing students' decision-making abilities is the most essential component of developing critical thinking skills; one does not exist without the other [21], and therefore this enhancement should be an intentional educational aim for all teachers.…”
Section: Decision-making As Learningmentioning
confidence: 99%
“…We document the ability students have to argument from higher-order reasoning and the opportunity that teachers have to engage their students in productive and socially and scientifically relevant discussions by using socialscientific issues. Studies on argumentation have found that students do not follow systematic decision-making processes (Lee & Grace, 2012;Hsu & Lin, 2017); nevertheless, the decisionmaking framework gives students motivation and knowledge, such that it is possible to find students showing systematic reasoning in discussions about science and technology (Gutierrez, 2017;Uluçinar, & Aypay 2016). This report shows how students can model the situation under discussion, seeking an appropriate background to present arguments about situations that impact particular human groups in real contexts.…”
Section: Discussionmentioning
confidence: 91%